Analisa Kepuasan Pengguna Aplikasi Inspekta Untuk Pelaporan K3 di PT PLN ULP Medan Selatan Dengan Metode Servqual - Maduma Sihaloho; Efa Rohani (TIN: Terapan Informatika Nusantara, 2022)
PLN is one of the institutions that aims to implement Occupational Health and Safety (K3). Currently, PLN is very consistent in making improvements to work processes, staff capabilities, work techniques, and various assets that can support the achievement of Occupational Health and Safety. One of the facilities that can help smooth the implementation of OHS perceptions and details at PLN is a site-based application called Inspecta. The motivation behind this research is to decide and evaluate the use of data innovations related to risk situations, dangerous behavior, accident conditions, accidents and work-related illnesses. The method used in this study is the servqual method, which is one method that can be used to measure the satisfaction of inspector users. The assessment is completed in five parts of regulatory quality, namely: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. From the results of the exploration that has been carried out, it was found that the inspection application provides benefits in building awareness and paying attention to OHS reporting